2014
DOI: 10.1080/0966369x.2014.970137
|View full text |Cite
|
Sign up to set email alerts
|

Gun rites: hegemonic masculinity and neoliberal ideology in rural Kansas

Abstract: Drawing upon empirical data from a qualitative research project in Southeast Kansas, this paper employs feminist and decolonial theories to analyse the interlocking relationality of hegemonic masculinity, neoliberal ideology, social conservatism, rurality, and gun culture. The first goal is to shed light on the subordinating and marginalizing tendencies that arise as a result of gendered conceptions of gun use. The second aim is to illustrate how gun culture is normalized, and often valorized, through individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 58 publications
(36 reference statements)
0
27
0
2
Order By: Relevance
“…In short, despite an interest in guns, my informants articulated that they did not consider these tools as socially central as the experiences they formed with them. While many shooters in North America pay lip service to this gun-as-tool discourse (Gahman 2015;Springwood 2014), the behaviour of my informants suggests they took this discourse seriously. While I always saw my informants ensure that their handguns or rifles were emptied of bullets before handing thembecause, I was told, even when a semiautomatic gun is not loaded with a mag it is possible for a bullet to be held in the chamber of the weapon -I witnessed instances where even quite expensive guns were unceremoniously dropped by shooters when they were done using them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, despite an interest in guns, my informants articulated that they did not consider these tools as socially central as the experiences they formed with them. While many shooters in North America pay lip service to this gun-as-tool discourse (Gahman 2015;Springwood 2014), the behaviour of my informants suggests they took this discourse seriously. While I always saw my informants ensure that their handguns or rifles were emptied of bullets before handing thembecause, I was told, even when a semiautomatic gun is not loaded with a mag it is possible for a bullet to be held in the chamber of the weapon -I witnessed instances where even quite expensive guns were unceremoniously dropped by shooters when they were done using them.…”
Section: Methodsmentioning
confidence: 99%
“…Yet a dominant tendency is to dwell on what are construed as the negative aspects of so-called gun culture (Patrick 2007). Perspectives associating gun ownership with neoliberalism, social conservatism, and "hegemonic masculinity" (Gahman 2015) inform much of the current scholarly research connected with "gun culture." While my informants performed identities that fit with expressions of normative masculinity, and sometimes "conservative" ideas (like criticism of "liberal" gun laws), normative portrayals of gun culture did not neatly fit my experiences in the field.…”
Section: The Importance Of Talkmentioning
confidence: 99%
“…The political and cultural motivations to support gun rights are based in deeply conservative values that many in the Republican Party hold dear (Melzer 2009). Indeed, research has found that gun owners and gun rights advocates hold political and ideological beliefs that often closely align with the Republican Party, including views on religion, same-sex marriage, punitiveness in criminal justice sanctions, and social policies (DeZee 1983;Gahman 2015;Jiobu and Curry 2001;Mencken and Froese 2017;Micklethwait and Wooldridge 2005;Stroud 2012;Wright and Marston 1975;Young and Thompson 1995). Thus, while not all Republicans consider themselves ardent supporters of gun rights, the vast majority of gun rights supporters do find themselves to be strongly aligned with the Republican Party (Parker et al 2017).…”
Section: Political Partisanshipmentioning
confidence: 99%
“…Little qualitative research has been done to explore the experiences of gun owners in the United States. What does exist focuses on gun carrying, the culture of toxic masculinity, or some aspect of gun violence (Carlson 2015; Gahman 2015; Patton et al. 2019; Shapira and Simon 2018; Stroud 2012).…”
Section: Introductionmentioning
confidence: 99%